Progressive Steps in Reforming Indonesian Islamic Family Law Through Gender Studies - Azhari, Doni; Asmuni, Asmuni (Institut Agama Islam Negeri Metro, 2023)
This article examines Indonesia's urgent need to update Islamic family law to reflect modern dynamics, technological advancements, and universal justice principles. The primary goal of reform is to elevate women's status by upholding, defending, and expanding their rights in line with Sharia law. The research methodology examines the history and foundation of family law reform in the context of Islamic law through a review of the literature and document analysis. The primary forces behind Islamic law reform in Indonesia include the need to close legal gaps, the effects of economic globalization, and the influence of reformed Islamic legal thought. The study's conclusions include the identification of a number of particular areas within Islamic family law that need to be changed, such as women's rights in the home, divorce, and inheritance. In order to address gender inequality and create a society that is more inclusive and just, these reforms are thought to be essential first steps.